PELATIHAN PEMBUATAN KERAJINAN TANGAN SUSIRU DI DESA MIRA KEPULAUAN MOROTAI - Pasongli, Hernita; Tonra, Wilda Syam; Wahyudi, Dahlan; Aswan, Marwis; Tonra, Winda Syam; Kasiuhe, Jeane Christi; Ikhsan, Muhammad (Jurnal Terapan Abdimas, 2024)
Abstract. Mira Village is famous for its strong culture. The culture of Mira Village is the result of inheritance from ancestors, such as marriage culture, celebrations and handicrafts. The craftsmen in Mira Village produce a variety of crafts that are culturally valuable and also authentically typical of North Maluku. One of them is a typical North Maluku handicraft made from bamboo, namely susuru. Based on the importance of preserving local culture and the need for suriu craftsmen which are becoming increasingly scarce, training activities for making susiru handicrafts were initiated by Khairun University. This activity received funding from the Ministry of Education and Culture for Community Service in 2023 through the Community Empowerment by Students (PMM) scheme. The training will be held in August 2023 in 5 meetings. The initial activity location was at the Mira Village hall and the next meeting was at the residents' homes. The target of this activity is Mira Village housewives. The aim of this activity is to provide basic training in making susiru so that it is hoped that public interest can increase and increase the number of susiru craftsmen in Mira Village. The result of this activity is an increase in community understanding and skills. After this activity was completed, there were 5 craftsmen who were active in making susuru handicrafts.Abstrak. Desa Mira terkenal dengan budaya yang kental. Budaya Desa Mira merupakan hasil warisan dari nenek moyang seperti budaya perkawinan, hajatan sampai dengan kerajinan tangan. Para pengrajin di Desa Mira menghasilkan beragam kerajinan yang bernilai budaya dan juga otentik khas Maluku Utara. Salah satunya adalah kerajinan tangan khas Maluku Utara yang terbuat dari bambu yaitu susiru. Berdasarkan pentingnya melestarikan budaya lokal dan kebutuhan dari pengrajin suriu yang semakin hari semakin sedikit, maka kegiatan pelatihan pembuatan kerajinan tangan susiru diinisiasi oleh Universitas Khairun. Kegiatan ini memperoleh pendanaan Kemdikbudristek Pengabdian Kepada Masyarakat tahun 2023 melalui skim Pemberdayaan Masyarakat oleh Mahasiswa (PMM). Pelatihan dilaksanakan pada bulan Agustus 2023 sebanyak 5 kali pertemuan. Tempat kegiatan perdana di balai Desa Mira dan pertemuan berikutnya di rumah warga. Sasaran kegiatan ini adalah ibu- ibu rumah tangga Desa Mira. Tujuan dilaksanakan kegiatan ini adalah memberikan pelatihan dasar pembuatan susiru sehingga diharapkan ketertarikan masyarakat dapat meningkat dan menambah pengrajin susiru di Desa Mira. Hasil kegiatan berdasarkan hasil evaluasi adalah adalah pemahaman dan skill yang meningkat. Setelah kegiatan ini selesai, ada 5 pengrajin yang aktif membuat kerajinan tangan susiru.